2008
DOI: 10.1016/j.jcrysgro.2007.11.095
|View full text |Cite
|
Sign up to set email alerts
|

Cathodoluminescence study of ZnO wafers cut from hydrothermal crystals

Abstract: Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters Services, Directorate for Info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
9
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 18 publications
3
9
0
Order By: Relevance
“…As has been reported [15], under high power UV-laser excitation the ZnO nanocrystals located in the top layers can be heated up to about 40 K, while the temperature of the cold finger of the cryostat remains at 10 K. Thus, assignment of the A-line exactly to the first LO phonon replica of free excitons or to excitons bound at structural defects may depend on not only morphology of ZnO but also measurement conditions. The obtained results are partially supported by the CL measurements, which show that the A-line is composed of two overlapped bands related to point defects and the first LO phonon replica of the free exciton [22]. Nevertheless, additional experiments are necessary for understanding the origin of the A-line emission in detail.…”
Section: Resultssupporting
confidence: 58%
“…As has been reported [15], under high power UV-laser excitation the ZnO nanocrystals located in the top layers can be heated up to about 40 K, while the temperature of the cold finger of the cryostat remains at 10 K. Thus, assignment of the A-line exactly to the first LO phonon replica of free excitons or to excitons bound at structural defects may depend on not only morphology of ZnO but also measurement conditions. The obtained results are partially supported by the CL measurements, which show that the A-line is composed of two overlapped bands related to point defects and the first LO phonon replica of the free exciton [22]. Nevertheless, additional experiments are necessary for understanding the origin of the A-line emission in detail.…”
Section: Resultssupporting
confidence: 58%
“…20 Both CL and PL research on ZnO demonstrated that mechanical polishing leads to surface and near surface damage, which decreases near band edge (NBE) luminescence efficiency, and forms non-radiative recombination centers (NRRCs) and intrinsic defects such as zinc vacancy (V Zn ) and zinc interstitial (Zn i ). [10][11][12][13][14][15][16][17] PAS studies also show creation of dislocations and vacancy defects in the near and sub-surface region after polishing. 19 Recent DLTS measurements show that mechanical polishing introduced two defect levels at 1.0 and 1.2 eV below the conduction band edge E C whose densities subsequent hydrofluoric acid (HF) etching reduced substantially while restoring bulk carrier densities.…”
mentioning
confidence: 96%
“…Previous research also showed the soft nature of ZnO, [8][9][10] which significantly affects the wafer handling, processing, and manufacture of ZnO-based devices. Polishing induced damage has been investigated by cathodoluminescence (CL), [9][10][11][12][13][14][15] photoluminescence (PL), 16,17 ion channeling, 18 positron annihilation spectroscopy (PAS), 19 and deep level transient spectroscopy (DLTS). 20 Both CL and PL research on ZnO demonstrated that mechanical polishing leads to surface and near surface damage, which decreases near band edge (NBE) luminescence efficiency, and forms non-radiative recombination centers (NRRCs) and intrinsic defects such as zinc vacancy (V Zn ) and zinc interstitial (Zn i ).…”
mentioning
confidence: 99%
“…It is worth to remark that the 3.31 eV band and its phonon replicas present a high intensity, which suggests a lower concentration of defects. 49 Furthermore, the intensity of the DLE luminescence is much lower than the NBE luminescence, showing a very significant reduction in comparison with the DLE luminescence from ZnO nanorods grown on bare c-sapphire. In addition, this band denotes a shift towards high energies, from red to the yellow spectral range ($2.24 eV).…”
Section: B Zno Buffer Layer Effectmentioning
confidence: 96%